1335-P: Serum Granulin Concentrations Are Elevated in Subjects with Impaired Fasting Glucose, Impaired Glucose Tolerance, and Newly Diagnosed Diabetes - HSUAN CHOU, YU; HSU, YUNG-HAN; CHON CHAN, KA; WU, HUNG-TSUNG; OU, HORNG-YIH (Diabetes (New York, N.Y.), 2025)
Introduction and Objective: Although plasma Hemoglobin A1c (HbA1c) levels and the oral glucose tolerance test (OGTT) are conventional diagnostics for prediabetes, OGTT may be inconvenient for patients due to the need for multiple blood samples. In addition, individuals with impaired fasting glucose (IFG) and impaired glucose tolerance (IGT) may have a decline in β-cell function independent of HbA1c levels. Therefore, a biomarker for screening prediabetes is important. Granulin is associated with obesity and insulin resistance. However, the serum granulin concentrations in prediabetes and diabetes are still unknown. Thus, the aim of the present study was to investigate the relationship among granulin, IFG, IGT, and newly diagnosed diabetes (NDD). Methods: A total of 180 age- and sex-matched participants with NGT (n=47), IFG (n=45), IGT (n=48), and NDD (n=40) was recruited for this cross-sectional study. Serum granulin levels were measured by ELISA. Linear regression analysis was used to evaluate the relationship among granulin, IFG, IGT, and NDD. Results: Serum granulin concentrations were higher in IFG, IGT and NDD groups than those of NGT groups (249.3 ± 62.7, 247.1± 56.7, 232.1 ± 50.6 and 189.7±42.4 ng/ml). In multiple linear regression analysis, IFG (p<0.001), IGT (p<0.001) and NDD (p< 0.01) were the positively associated factors of serum granulin concentrations after adjusting for age, sex, body mass index, blood pressure, lipid profile, creatinine and alanine aminotransferase. Conclusion: Elevated serum granulin concentrations had a potential to be a novel biomarker for the screening of prediabetes.